Instrumented Wave Gliders for Air-Sea Interaction and Upper Ocean Research - Grare, Laurent; Statom, Nicholas M.; Pizzo, Nick; Lenain, Luc (Frontiers in Marine Science, 2021)
Over the last several years, the Air-Sea Interaction Laboratory at Scripps Institution of Oceanography has developed a fleet of wave-powered, uncrewed Wave Gliders (Liquid Robotics) specifically designed and instrumented for state-of-the-art air-sea interaction and upper ocean observations. In this study, measurement capabilities from these platforms are carefully described, compared, and validated against coincident measurements from well-established, independent data sources. Data collected from four major field programs from 2013 to 2020 are considered in the analysis. Case studies focusing on air-sea interaction, Langmuir circulations and frontal processes are presented. We demonstrate here that these novel, instrumented platforms are capable of collecting observations with minimal flow-structure interaction in the air-sea boundary layer, a region of crucial current and future importance for models of weather and climate.